2012
DOI: 10.1111/jace.12016
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Network Effect of Broadband Near‐Infrared Emission in Bi‐Doped B2O3GeO2 Glasses

Abstract: We report on the mixed network effect of broadband near-infrared (NIR) emission of Bi-doped borogermanate glasses. On excitation with 808 nm laser diode (LD) radiation, the fluorescence emission intensity at 1235 nm with a full width at half maximum (FWHM) of about 200 nm was found to vary with B 2 O 3 content, which agrees well with the variation tendency of the absorption intensity at 500 and 700 nm. The peak position and the intensity of the NIR emission depend strongly on the excitation wavelength. Two kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 31 publications
4
25
0
Order By: Relevance
“…Zhang et al. suggested that the near infrared luminescence peaks at ~1100 and ~1260 nm can be attributed to Bi + and Bi 0 . Xu et al.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Zhang et al. suggested that the near infrared luminescence peaks at ~1100 and ~1260 nm can be attributed to Bi + and Bi 0 . Xu et al.…”
Section: Resultssupporting
confidence: 90%
“…On the basis of our research, we conclude that the NIR emission peaks at ~1140, ~1240, and ~1440 nm may originate from Bi + , Bi 0 , and (Bi 2 ) 2− , respectively. Figure shows the energy levels of Bi + , Bi 0 and (Bi 2 ) 2− based on the absorption, emission spectra of our research and some literatures . We suggest that the emissions centered at about 1140, 1240, and 1440 nm can be ascribed to 3 P 1 → 3 P 0 transition of Bi + , 2 D 3/2 → 4 S 3/2 transition of Bi 0 , and 10→ 3 Π 2g transition of (Bi 2 ) 2− , respectively.…”
Section: Resultssupporting
confidence: 50%
“…The center of the emission bands is located at 1280 nm, and the FWHM of the emissions is about 270 nm. The ultrabroadband emissions have been attributed to electronic transitions of low valence Bi or Bi clusters [30][31][32][33], but the exact origin would need further investigation. Furthermore, when excited at 808 nm, the ultrabroadband emission intensity of Bi first increases as the doping concentration of Bi 2 O 3 is increased, reaching a maximum at 3.5 mol% Bi 2 O 3 doping, and then decreases when the Bi 2 O 3 content is further increased.…”
Section: Resultsmentioning
confidence: 99%
“…. Besides for the typical absorption band of OH − group at ~3500 cm −1 , the strong absorption at ~735 cm −1 is ascribed to the bending and stretching vibrations of T–O–T (T = B, Ge) linkages, while the high‐frequency region of IR spectra centered at 1160 cm −1 correspond to the vibrations of [BO 3 ] triangle group . However, the similar shape of normalized IR spectra cannot give the evolution of glass structure in detail, Raman spectra are carried out and discussed in the next paragraph.…”
Section: Resultsmentioning
confidence: 99%